The Persianate world : the frontiers of a Eurasian lingua franca - Green, Nile (University of California Press, 2019)
"Persian is one of the great lingua francas of world history. Yet despite its recognition as a shared language across the Islamic world and beyond, its scope, impact and mechanisms remain underexplored. A world historical inquiry into pre-modern cosmopolitanism, The Persianate World traces the reach and limits of Persian as a Eurasian language in a comprehensive survey of its geographical, literary, and social frontiers. From Siberia to Southeast Asia, and between London and Beijing, this book shows how Persian gained, maintained, and finally surrendered its status to imperial and vernacular competitors. Capturing the Persianate as process, fourteen essays trace Persian's interactions with Bengali, Chinese, Turkic, and Punjabi, to identify the forces that extended 'Persographia, ' the domain of written Persian. Spanning the ages' expansion and contraction, The Persianate World offers a critical survey of both the supports and constraints of one of history's key languages of global exchange"--Provided by publisher.